Identification of Bola Class I molecules restricting cytotoxic T lymphocyte responses to a theileria parva vaccine candidate. - Mwakubambanya, R.S. (Jomo Kenyatta University of Agriculture and Technology, 2005)
Theileria parva is an intracellular protozoan parasite that infects and transforms bovine lymphocytes, causing a severe Iymphoproliferative disease, East Coast fever (ECF). A robust immunity against ECF acquired after recovery is thought to be conferred by cytotoxic T lymphocytes (CTLs) specific to schizontinfected lymphocytes. Efforts are underway to develop a subunit vaccine based upon CTL target schizont antigens and to date eight CTL vaccine target antigens have been identified for evaluation. MHC class I genes encode cell surface glycoproteins that bind and present antigenic peptides to CTLs. The evaluation of these candidate vaccine antigens is to be carried out in a number of cattle of diverse BoLA class I genotypes. In this antigen evaluation process, knowledge of the BoLA class I genes restricting the CTL responses to schizont antigen is important to the development of a subunit vaccine against T. parva. However, a rapid test to define and identify BoLA class I phenotypes is lacking. The aim of this study was to identify BoLA class I genes that restrict CTL epitopes on Tp2, one of the candidate vaccine antigens and contribute to the development of a rapid PCR-based BoLA typing test. BoLA class I cDNAs were generated fromcattle immune to T. parva from which Tp2-specific CTL had been generated. BoLA class I cDNAs were co-transfected with Tp2 DNA into COS-7 cells and recognition by Tp2 specific CTL was assessed by IFN-y Enzyme Linked Immunospot and cytotoxicity assays. Two potentially novel BoLA class I genes restricting two different CTL epitopes on Tp2 sequence were identified and termed BoLA T2a and T2b. These BoLA class I cDNAs are now being used to develop PCR-based tests to identify cattle to be used in the evaluation of the vaccine potential of Tp2.